Clinical Characteristics of Proliferative Diabetic Retinopathy and Outcome of Pars Plana Vitrectomy in Proliferative Diabetic Retinopathy - Thapa, Raba; Sharma, Sanjita; Pradhan, Eli; Duwal, Sushma; Paudyal, Govinda (Journal of Nepal Health Research Council, 2024)
Background: Proliferative diabetic retinopathy is a leading cause of blindness among people with diabetes. The study aimed to assess the clinical characteristics of proliferative diabetic retinopathy and outcome of pars plana vitrectomy in Proliferative diabetic retinopathy. Methods: A prospective study was conducted from September 2019 to December 2021 among consecutive cases of proliferative diabetic retinopathy who underwent pars plana vitrectomy at a tertiary eye care center. Study was conducted after ethical approval from Institutional Review Committee. Detailed systemic and ocular history, visual acuity, ocular findings under mydriasis, surgical procedures, and outcome following pars plana vitrectomy were recorded. Cases were followed up regularly until one year after the pars plana vitrectomy. Results: Total of 83 cases (89 eyes) of proliferative diabetic retinopathy were enrolled in the study. The mean age was 53 years ±9.7 SD, ranging from 26 years to 72 years. Males comprised of 62.7% cases. Type two diabetes comprised of 94% of cases. Indications for pars plana vitrectomy were; mixed vitreous hemorrhage and tractional retinal detachment (38.2%), non-clearing vitreous hemorrhage (38.1%), and tractional retinal detachment only (24.7%). Pre-operative intra-vitreal anti-vascular endothelial growth factor was given in 78.65% eyes and pan retinal photocoagulation in 58.42% eyes. The anatomical success was achieved in 95.5% eyes, visual improvement in 68.54%, static in 14.6% and worsened in 16.86% of eyes. About 15.7% of eyes had some form of post- operative complications. Conclusions: Vitreous hemorrhage with tractional retinal detachment, persistent vitreous hemorrhage and tractional retinal detachment involving macula were the common indication of pars plana vitrectomy among cases of Proliferative diabetic retinopathy. Anatomical success and visual acuity improvement can be achieved in majority of the eyes following PPV in Proliferative diabetic retinopathy. Keywords: Anatomical outcome; pars plana vitrectomy; proliferative diabetic retinopathy; visual outcome.